Consumó de h y su incidencia en la salud mental de un adolescente de 20 años en la ciudad de Quevedo - Rodriguez Smith, Darwin Javier (2022)
The use of drug "h" is a problem that grows over time and mainly affects children and adolescents. In Ecuador, the growth of the consumption of this drug is alarming and it is not something that only happens in the country, because it is a phenomenon that affects the world. For this reason, the present case study was carried out with the objective of analyzing the incidence that the consumption of "h" has on the mental health of a 20-year-old adolescent in the city of Quevedo and providing psychological strategies that help young consumers. to improve the quality of life. The research is carried out through mixed methodology, because techniques that allow the collection of both qualitative and quantitative data were used. The methods are: clinical and psychometric. On the other hand, the techniques used are: semi-structured interview, clinical observation, clinical history, scale (ASSIST V3.0), Beck depression inventory and H.T.P. The results of the investigation indicate that the patient meets the diagnostic criteria according to DSM-5 for a disorder belonging to the group of depressive disorders. The young man's symptoms have an evolution period of two months. In conclusion, the consumption of "h" influences the mental health of the 20-year-old, causing alterations that produce signs and symptoms in the subject that affects the quality of life at the family, school, social level, among other important areas in the person's life.